Pulmonary adenocarcinoma associated with Guillain–Barré syndrome: A case report. Issue 21 (May 2018) - Wang, Yuhuan; Yang, Sijia; Fang, Liang; Liu, Yang; Jiang, Gang; Ding, Xiaoyan; Wei, He; Liu, Min
Abstract: Rationale: Guillain-Barré Syndrome (GBS) as a paraneoplastic manifestation of small cell lung cancer has been published several times, while paraneoplastic GBS accompanied by pulmonary adenocarcinoma is rare. Patient concerns: An 80-year-old male was hospitalized with a 2-week history of fever and 10-day history of progressive ascending muscle weakness in the legs and arms. The patient felt weakness in legs at first when he was still able to move around, but the symptoms gradually progressed to the arms. At the time of office visit, he could no longer walk or hold up objects, and had absent deep-tendon reflexes as well as weakened left lung breath sounds. Diagnoses: Confirmed by the Cerebrospinal fluid (CSF) and electromyography examination, the patient was originally admitted into our hospital for GBS. However, radiology and histological examination revealed pulmonary adenocarcinoma. He was relatively old and confirmed to have pulmonary adenocarcinoma with simultaneously detected GBS, so was considered to be a paraneoplastic syndrome, rather than pure GBS. Interventions: The patient was treated with methylprednisolone at 80 mg Qd for 10 consecutive days, which resulted in improvement in arms, then tapering to lower doses for 3 months. Outcomes: The patient showed temporary relief until relapse 6 months later, when the patient gave up treatment. Lessons: To our knowledge, this is the first case of pulmonary adenocarcinoma that was diagnosed based on Guillain-Barré-like syndrome, which is very difficult to diagnose and treat. We suggest that elderly patients with GBS should not be considered as simple GBS and should be thoroughly examined to exclude systemic diseases, especially paraneoplastic neurological syndromes. In addition, the elderly should be screened regularly for tumor markers.